Do Extra-Platelet Sources Contribute to the Plasma Level of Thrombospondin? - Dawes, J; Pratt, D A; Dewar, M S; Preston, F E (Thrombosis and Haemostasis, 1988)
Thrombospondin, a trimeric glycoprotein contained in the platelet α-granules, has been proposed as a marker of in vivo platelet activation. However, it is also synthesised by a range of other cells. The extraplatelet contribution to plasma levels of thrombospondin was therefore estimated by investigating the relationship between plasma thrombospondin levels and platelet count in samples from profoundly thrombocytopenic patients with marrow hypoplasia, using the platelet-specific α-granule protein β-thromboglobulin as control. Serum concentrations of both proteins were highly correlated with platelet count, but while plasma β-thromboglobulin levels and platelet count also correlated, there was no relationship between the number of platelets and thrombospondin concentrations in plasma. Serial sampling of patients recovering from bone marrow depression indicated that the plasma thrombospondin contributed by platelets is superimposed on a background concentration of at least 50 ng/ml probably derived from a non-platelet source, and plasma thrombospondin levels do not simply reflect platelet release.
Keywords: Platelet; Thrombospondin; β-thromboglobulin; Marrow hypoplasia